Comparison between Spine Students book one and Smile student book one on teachers’ point of view - Dr. Mohammed Alameen Yousif Kiber; Dr. Mohi Eldeen Ahmed Abd Elrahman Ahmed; Dr. Abdelrahman Mohammedain Abdelrahman Ahmed (White Nile Journal for Studies and Research, 2021)
This paper aimed to compare and contrast between spine one and smile one which are used to teach English language at Sudanese basic school. Spine one has been replaced by smile one in late decade. The motivation behind this study lies in the belief this comparison shed important light on the syllabus contents of teaching English as a foreign or second language, the objectives , and the activities. A teachers' questionnaire was used to collect the teachers stand points about the contents, objectives , and the learning activities of spine and smile to identify some of the differences among these textbooks and to explore the findings which reflect English language teaching curriculum in Sudan . the data was analyzed by adopting (SPSS) program. The results reveal the following: spine and smile one are different in term of objectives. spine and smile one are different in term of content. spine and smile one are different in term of activities .Moreover, smile one has a general trends as well as the unique features which is different from spine one. The researchers recommend that smile should be supported and encouraged as it contains modern rends in teaching English. As well as contains clear objectives and effective activities in accordance to the general objectives of teaching English